2018
DOI: 10.7241/ourd.20183.13
|View full text |Cite
|
Sign up to set email alerts
|

Unsusual manifestation of terra firme-forme dermatosis – upper eyelid and orbital rim

Abstract: Terra firme-forme dermatosis is a benign exogenous dermatosis found in all age-groups. The typical localizations include neck, face, trunk and ankles. Here we report on an 88-year-old male with a medical history of stroke and paraplegia of the legs who presented with asymptomatic, hyperkeratotic and slightly hyperpigmented lesions on his upper lids. Wiping of skin with alcohol pads completely removed the lesions confirming the diagnosis of terra firmeforme dermatosis of upper eyelids. Although affection of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The title and abstract of the 102 items were screened, and 69 were considered eligible for full‐text assessment. Of the 69 studies, 64 were included in the systematic review 1–63 . The studies were published between 1987 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The title and abstract of the 102 items were screened, and 69 were considered eligible for full‐text assessment. Of the 69 studies, 64 were included in the systematic review 1–63 . The studies were published between 1987 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…According to Erkek et al, TFFD is an unintentional variant of DN, and the arbitrary boundaries between the two entities, based on the presence/absence of regular hygiene habits, become blurred. Two reports included in this review adopted this theory and used TFFD and DN as interchangeable synonyms 28,55 . Shan et al resume the name, already reported in the Chinese literature, of dirt adherent disease to encompass a common presentation of thick, asymptomatic, dark brown adherent lesions characterized by hyperkeratosis with follicular plugs on histology 68 .…”
Section: Discussionmentioning
confidence: 99%